1995
DOI: 10.1007/bf00032299
|View full text |Cite
|
Sign up to set email alerts
|

Light-regulated pigment interconversion in pheophytin/chlorophyll-containing complexes formed during plant leaves greening

Abstract: Upon illumination of etiolated maize leaves the photoconversion of protochlorophyllide Pchlide 655/650 into chlorophyllide Chlide 684/676 was observed. It was shown that chlorophyllide Chlide 684/676 in the dark is transformed into pheophytin Pheo 679/675 and chlorophyll Chl 671/668 by means of two parallel reactions, occurring at room temperature: Chlide 684/676. The formed pheophytin Pheo 679/675 was unstable and in the dark was transformed into chlorophyll Chl 671/668 in a few seconds: Pheo 679/675 → Chl 67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…20,21 However, the Pheo a/Chl a ratio, which they estimated from the fluorescence excitation spectra, was as high as 50%, which is far from the value obtained here (about 0.47%). Such a discrepancy might, at least partially, be due to a difference in the illumination conditions.…”
Section: Discussioncontrasting
confidence: 92%
“…20,21 However, the Pheo a/Chl a ratio, which they estimated from the fluorescence excitation spectra, was as high as 50%, which is far from the value obtained here (about 0.47%). Such a discrepancy might, at least partially, be due to a difference in the illumination conditions.…”
Section: Discussioncontrasting
confidence: 92%
“…Here, we present further evidence of this smart P-allocation strategy, which is summarized in Figure 7. In young H. prostrata leaves, pheophytin was highly abundant while chlorophylls only accumulated as the leaves matured, a situation similar to that found in maize, where pheophytin accumulates in etiolated leaves prior to light-regulated conversion into chlorophyll (Ignatov and Litvin, 1995). The chlorophyll a/b ratio was also very low in young H. prostrata leaves (Sulpice et al, 2014) and resembled ratios found in shade leaves, with 2-fold lower CO 2 assimilation rates (Lichtenthaler et al, 2007).…”
Section: Young H Prostrata Leaves Show Delayed Development Of Functimentioning
confidence: 57%